Effects of superheated steam processing on the physicochemical properties of sea rice bran - Cao, Xiaohuang (Food science and technology international = Ciencia y tecnologia de los alimentos internacional, 2023)
Sea rice bran powder is a new type of instant food additive. Currently, its solubility is low, and its flavor is not pleasant. Superheated steam cooking is a promising treatment in cellulose-rich substances, which essentially improves quality. To gain better sea rice bran powder, physicochemical properties of sea rice bran were investigated using 100 °C, 110 °C, 120 °C, and 130 °C superheated steam treatments for 10, 20, 30, and 40 min. After the treatment, these samples were cooled down, dried, and milled to assess sea rice bran powder's product qualities. Profiles of odor, taste, aroma, and aliphatic acids were determined using e-nose, e-tongue, and gas chromatography-mass spectroscopy. Results revealed that superheated steam brought new profiles of odors and tastes for consumers. Superheated steam treatment was found to decrease swelling capacity. Methane (2,2,4,6,6-pentamethyl, heptane) was seen as a significant odor component, whereas umami and bitterness were considered considerable taste components. Superheated steam treatment retained higher content of aliphatic acids: saturated fatty acids 218-204 mg/100 g and unsaturated fatty acids 830-781 mg/100 g. This study discovered that superheated steam is suitable for processing rice bran as food ingredients; 100 °C-120 °C and 10-30 min could be suggested for suitable cooking sea rice bran